2019
DOI: 10.3390/su11133729
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Ecological Niche and Factors Affecting Agroforestry Practice Adoption in Different Agroecologies of Southern Tigray, Ethiopia

Abstract: This study was carried out in the southern zone of Tigray to identify and characterize traditional common agroforestry practices and understand the existing knowledge of farm households on the management of trees under different agroforestry in different agroecologies. We conducted reconnaissance and diagnostic surveys by systematically and randomly selecting 147 farming households in the three agroecologies of the study area. A logit regression model was employed to determine how these factors influence farme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 36 publications
(41 reference statements)
3
39
0
Order By: Relevance
“…In addition, evidences show that other factors and variables affect tree plantation as well as other sustainable land use practices. Land size [7,31,[47][48][49][50][51][52][53], tree nursery [50,54], extension services and getting consultancy [28,31,49,52,55], age [52,56,57], and education [47,50,51,53] are major factors for sustainable land use practices including tree plantation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, evidences show that other factors and variables affect tree plantation as well as other sustainable land use practices. Land size [7,31,[47][48][49][50][51][52][53], tree nursery [50,54], extension services and getting consultancy [28,31,49,52,55], age [52,56,57], and education [47,50,51,53] are major factors for sustainable land use practices including tree plantation.…”
Section: Introductionmentioning
confidence: 99%
“…The respondents reported that population increase, shortage of land for plantation, livestock grazing system (open grazing), lack of seedling, and termite infestation are the major forestry constraints [62]. This result shows that about 39.70%, 35.30%, and 25.00% of respondents were reported due to increase population, shortage of land, and open grazing as the main important constraints, respectively.…”
Section: Major Forestry and Agroforestry Constraintsmentioning
confidence: 94%
“…Number of active family members: Having more active family members decreases the level of farmers' interaction with water users' associations by about 5%. This result is unexpected as active family members can alleviate any labor shortage and a large family size implies a high availability of labor [78] that exists within a household. The water users' associations are supposed to support farmers in any endeavors related to irrigation facilities, with the farmers expected to clean the irrigation canals themselves.…”
Section: Personal and Demographic Characteristicsmentioning
confidence: 99%